Digital Transformation and SME Growth in Emerging Markets - Rampaul , Kiara (Journal of Emerging Markets and Management, 2025)
Small and medium-sized enterprises (SMEs) are pivotal to local economic resilience, employment generation, and innovation in emerging markets. As urbanisation accelerates and digital economies expand, digital transformation emerges not only as a technological imperative but as a developmental and spatial strategy. This paper explores the evolving relationship between digitalisation and SME growth in developing contexts, drawing from the perspective of urban and regional planning. While digital tools offer SMEs new pathways to participate in broader markets and streamline operations, their uptake is often constrained by infrastructure deficits, regulatory uncertainty, and spatial disparities in digital access. Through a critical review of scholarly literature, policy documents, and institutional reports, this study identifies key barriers and strategic responses associated with SME digitalisation. Particular attention is paid to how digital infrastructure, governance environments, and urban–rural linkages influence the efficacy of digital transformation efforts. Strategies such as fintech integration, digital hubs, and public–private partnerships are evaluated for their relevance in spatially diverse regions. The findings highlight the need for place-based, multi-scalar policy responses that align digital transformation initiatives with inclusive urban development and spatial equity. This study contributes to a more integrated understanding of digital development, one that merges technology with territorial planning and offers insights for policymakers, planners, and SME practitioners navigating the digital economy in emerging markets.